The impact of inflammatory and oxidative stress biomarkers on the sympathetic nervous system in severe coronary atherosclerosis - Boieriu, Alexandra Maria; Dumitrel Luca, Cezar; Neculoiu, Carmen Daniela; Ţînţ, Diana (Frontiers in Cardiovascular Medicine, 2024)
Objective: The present study aimed at evaluating the association between sympathetic nervous system activation (SNS) and the severity of coronary artery disease (CAD). In addition, we tested the hypothesis that inflammation and oxidative stress influence the SNS activation.Methods: Adult patients with severe CAD scheduled for coronary artery bypass graft (CABG) surgery were enrolled. SYNTAX I score was calculated based on coronary angiography. Systemic activation of the SNS was estimated through circulating levels of norepinephrine (NE). Plasma levels of pro-inflammatory cytokines (IL 1β, IL 6 and HIF 1α) and oxidative stress molecules (SOD-1 and LOX-1) were obtained prior to surgery.Results: Circulating NE levels were significantly correlated with the severity of CAD, as assessed by the SYNTAX I score (p 0.002; r 0.329). Elevated levels of circulating pro-inflammatory markers were significantly correlated with increased NE concentrations (for IL-1β: p < 0.001, r = 0.49; for IL-6 and NE: p = 0.003, r = 0.32; for HIF-1α and NE: p = 0.049, r = 0.21). Additionally, oxidative stress molecules were associated with circulating NE levels (for SOD-1 and NE: p = 0.016, r = 0.26; for LOX-1 and NE: p = 0.004, r = 0.31).In patients with CAD referred for CABG, SNS activation, indicated by plasma NE levels, was correlated with disease severity as assessed by the SYNTAX I score, as well as with markers of inflammation and oxidative stress. This suggests that inflammation, oxidative stress, and SNS activation form an interconnected network, with each component influencing the others.It might be of interest to develop a scoring system including inflammation and oxidative stress markers to identify patients that require a more aggressive approach to lower inflammation, oxidative stress and modulate the sympathetic nervous system. This could be of use especially in the setting of a scheduled intervention -such as CABG surgery.